Activated carbon material for adsorbing heavy metals in soil and manufacturing process of activated carbon material

By modifying activated carbon and tourmaline powder, the problem of poor adsorption of heavy metals in acidified soil in the prior art was solved, and the effect of efficient adsorbing heavy metals in acidic soil was achieved.

CN119455894AActive Publication Date: 2025-02-18GUANGDONG AGRI ENVIRONMENT INSPECTION & TESTING CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411640881.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing activated carbon materials have poor adsorption effect on heavy metals in acidified soil, and the adsorption capacity of modified sludge activated carbon is reduced in acidified soil.

Method used

The preparation method of modified activated carbon materials includes pretreatment of activated carbon and modification by polyaspartic acid, increasing surface carboxyl and sulfonate groups, and increasing adsorption sites. At the same time, modified tourmaline enhances its chelation and adsorption ability to heavy metals by introducing thiol, amide and pyridine groups.

Benefits of technology

Modified activated carbon materials significantly improve the adsorption capacity of heavy metals in acidic soil, reduce the water-soluble and exchangeable content of heavy metals, enhance the fixation effect on heavy metals, and achieve stable and efficient heavy metal adsorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455894A_ABST
    Figure CN119455894A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of soil heavy metal adsorption, and discloses an activated carbon material for adsorbing soil heavy metals and a manufacturing process thereof.The activated carbon material is obtained by modifying activated carbon, modified activated carbon with the large specific surface area, rich pores and multiple adsorption sites is obtained, and the surface of the modified activated carbon is provided with carboxylic acid groups and sulfonate groups; heavy metals are adsorbed, so that the water-soluble content and the exchangeable content of the heavy metals are reduced; the tourmaline powder is modified to obtain a mineral addition component containing rich chelating groups, the mineral addition component and heavy metal generate chelation, the pH value of soil can be increased, the soil is promoted to be neutral, and the mobility, the effective state content and the bioavailability of the heavy metal are reduced, so that the prepared activated carbon material has an excellent heavy metal adsorption effect; the method is especially suitable for acidifying heavy metal soil.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil heavy metal adsorption, and in particular to an activated carbon material for adsorbing soil heavy metals and a manufacturing process thereof. Background Art

[0002] Soil is an important part of the natural ecosystem. It is an important natural resource for humans and the cornerstone of agricultural production. It is vital to survival and development. In recent years, with the continuous development of urbanization and industrialization, agricultural sewage irrigation, mining waste, heavy metals enter the soil through atmospheric deposition, and the abuse of pesticides and fertilizers have accumulated, resulting in soil contamination by heavy metals. Heavy metals include cadmium, lead, chromium, copper, mercury, etc., which are difficult to degrade, easy to accumulate and highly toxic. Once the concentration of heavy metals in the soil exceeds the purification and holding capacity of the soil itself, it will cause damage to the soil structure, reduction of biodiversity and ecological imbalance, affecting the growth and quality of crops, reducing agricultural productivity, and can accumulate in the human body through the food chain, interact with biological molecules in the body, posing a threat to human life and health. Therefore, the adsorption of heavy metals in the soil is crucial to protecting human health and the ecological environment, and is of great research significance.

[0003] Activated carbon is a common adsorbent that can be used for air purification, gas separation, and adsorption of heavy metals in water or soil. It contains a variety of rich functional groups on its surface, has a well-developed pore structure, has a large specific surface area, is stable, is acid-resistant, and is renewable. However, the adsorption capacity of activated carbon is limited and it is easily saturated, so the adsorption effect on heavy metals is poor. When the soil is acidified, it has limited effect on reducing the effective state of heavy metal ions in the soil. The patent with publication number CN109231758B discloses a modified sludge activated carbon heavy metal adsorption material, which is activated by phosphoric acid treatment and activated carbon. The invention adopts three steps of chemical treatment and modification treatment to improve the adsorption of heavy metal ions. The prepared adsorption material has micropore, mesopore and macropore structures, which not only has adsorption effect on heavy metal ions, but also can expand the scope of use, and can have efficient adsorption effect on macromolecular pollutants. The adsorption material has stable performance, and the sludge can be recycled and utilized as a resource. However, the patent does not take into account that the effective state of heavy metals in acidified soil will increase, and the adsorption capacity of modified sludge activated carbon will decrease. Therefore, the present invention provides an activated carbon material that can play an excellent role in adsorbing heavy metals in acidic soil. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide an activated carbon material for adsorbing heavy metals in soil and a manufacturing process thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] An activated carbon material for adsorbing heavy metals in soil comprises the following raw materials in parts by weight: 35-50 parts of modified activated carbon, 10-15 parts of mineral additive components, 4-8 parts of natural composite glue, 2-4 parts of calcium carbonate and 3-6 parts of zeolite powder.

[0007] Furthermore, the preparation method of the modified activated carbon comprises the following steps:

[0008] Step S1: adding activated carbon to concentrated nitric acid, stirring and mixing for 2-4 hours, filtering, washing, and drying to obtain pretreated activated carbon;

[0009] Step S2: Add the pretreated activated carbon and polyaspartic acid to N,N-dimethylformamide, mix evenly, and ultrasonically vibrate for 10-30 minutes, then add 3-hydroxypropanesulfonic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, start stirring, control the stirring rate to 500-650r / min, stir for 4-6 hours, separate the product, wash, and dry to obtain modified activated carbon.

[0010] By adopting the above technical scheme, after the activated carbon is treated with concentrated nitric acid, surface impurities are removed, the specific surface area and pore capacity are increased, the oxygen-containing groups are increased, and the polyaspartic acid can react with the oxygen-containing groups on the surface of the activated carbon to achieve the modification of the activated carbon by polyaspartic acid. Under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the hydroxyl group in the 3-hydroxypropanesulfonic acid structure can undergo esterification reaction with the carboxyl group in the polyaspartic acid structure to obtain modified activated carbon. The modified activated carbon prepared by the present invention uses activated carbon as a matrix, and the activated carbon has a large specific surface area and rich pore structure. The surface of the modified activated carbon contains a large number of carboxyl groups and sulfonate groups, which effectively increases the adsorption sites of the activated carbon for adsorbing heavy metals, thereby improving the ability of the activated carbon to adsorb heavy metals. In the subsequent use process, the carboxylic acid group and the sulfonate group are used to adsorb and react with the heavy metals, thereby reducing the water-soluble and exchangeable content of the heavy metals, thereby achieving the purpose of fixing the heavy metals, and having the effect of stably and efficiently adsorbing heavy metals.

[0011] Furthermore, in step S1, the mass fraction of concentrated nitric acid is 60-65%.

[0012] Furthermore, in step S2, the ultrasonic frequency during the ultrasonic oscillation is 60-80kHz.

[0013] Furthermore, the method for preparing the mineral additive component comprises the following steps:

[0014] Step T1: Disperse tourmaline powder in dimethyl sulfoxide to form a uniform dispersion, add mercaptosuccinic acid and a catalyst, stir and mix evenly, raise the temperature to 90-95° C., react for 3-5 hours, filter, wash, and dry to obtain modified tourmaline powder;

[0015] Step T2: Add the modified tourmaline powder into N,N-dimethylformamide, and after uniform dispersion, add aminopyridine compounds, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react for 3-5 hours, discharge, wash, and dry to obtain a mineral additive component.

[0016] By adopting the above technical scheme, the hydroxyl groups on the surface of the tourmaline powder can undergo an esterification reaction with the carboxyl groups in the structure of mercaptosuccinic acid under the action of a catalyst to obtain a modified tourmaline powder having carboxyl groups and mercapto groups on the surface; under the action of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, the carboxyl groups on the surface of the modified tourmaline powder can undergo an amidation reaction with the amino groups in the structure of aminopyridine compounds to obtain a mineral additive component. The mineral additive component prepared by the present invention is prepared by modifying tourmaline powder, and the tourmaline powder can adsorb heavy metals in the soil through ion exchange. After modification, thiol, amide and pyridine groups are introduced on the surface of the tourmaline powder, and these groups can produce chelation with heavy metals in the soil, adsorb and fix heavy metal ions in the soil. The tourmaline powder and the introduced pyridine groups can effectively improve the pH value of the soil, promote the soil to be neutral, increase the affinity of the soil for heavy metals, passivate the heavy metals in the soil, reduce the mobility and effective content of the heavy metals in the soil, thereby reducing the biological effectiveness of the heavy metals in the soil, and the fixation effect on the heavy metals in the soil is stable, no secondary pollution is generated, and there is a synergistic effect with the modified activated carbon, thereby increasing the adsorption amount of heavy metals by the activated carbon material.

[0017] Furthermore, in step T1, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

[0018] Furthermore, in step T2, the aminopyridine compound is any one of 2-aminopyridine, 3-aminopyridine or 4-aminopyridine.

[0019] Furthermore, the preparation method of the natural composite rubber is as follows:

[0020] Add agar and arabinoxylan into deionized water, raise the temperature to 60-70°C, stir and mix for 0.5-1h, add sodium tripolyphosphate, continue stirring for 2-4h, cool to room temperature, discharge, and obtain a natural composite glue.

[0021] By adopting the above technical scheme, sodium tripolyphosphate is used to promote the cross-linking of hydroxyl groups in the structure of agar and arabinoxylan to obtain a natural composite glue. The natural composite glue prepared by the present invention has a cross-linked network structure, which greatly improves the bonding strength, avoids the use of natural agar or arabinoxylan as an adhesive alone, which has insufficient bonding strength, resulting in excessive addition and blocking the pores of modified activated carbon, mineral additive components and zeolite powder, thereby having a negative impact on the adsorption of heavy metals in the soil.

[0022] A manufacturing process of an activated carbon material for adsorbing heavy metals in soil comprises the following steps:

[0023] Step 1: Add modified activated carbon, mineral additive components, calcium carbonate and zeolite powder into a mixer, stir and mix for 10-30 minutes, add natural composite rubber, keep the stirring rate unchanged, and continue stirring for 1-3 hours to obtain a mixed base material;

[0024] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 70-90°C for 4-6 hours, and cool it to room temperature to obtain the activated carbon material.

[0025] Furthermore, in step 1, the stirring rate is 150-300 r / min.

[0026] Beneficial effects of the present invention:

[0027] The present invention modifies activated carbon to obtain modified activated carbon containing carboxyl and sulfonate groups, thereby increasing adsorption sites, improving the ability to adsorb heavy metals, and reducing the water-soluble and exchangeable contents of heavy metals. By modifying tourmaline powder, the modified activated carbon can produce a chelating effect with heavy metals, increase the pH value of soil, passivate soil heavy metals, reduce the mobility and effective content of soil heavy metals, have a synergistic effect with the modified activated carbon, increase the adsorption amount of heavy metals, and thus make the prepared activated carbon material have an excellent heavy metal adsorption effect, and is particularly suitable for acidified heavy metal soils.

[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0030] Figure 1 This is the infrared spectrum of the mineral added components in the present invention. DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The preparation methods of modified activated carbon, mineral additive components and natural composite rubber in the following examples and comparative examples are as follows:

[0033] 1. Preparation of modified activated carbon

[0034] Step S1: adding 5.2 g of activated carbon into concentrated nitric acid with a mass fraction of 65%, stirring and mixing for 3 hours, filtering, washing, and drying to obtain pretreated activated carbon;

[0035] Step S2: Add 5 g of pretreated activated carbon and 3.6 g of polyaspartic acid to N,N-dimethylformamide, mix well, and ultrasonically vibrate at a frequency of 60 kHz for 20 min. Then, add 2 g of 3-hydroxypropanesulfonic acid, 0.4 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine. Start stirring and control the stirring rate to 600 r / min. After stirring for 5 h, separate the product, wash it, and dry it to obtain modified activated carbon.

[0036] The activated carbon and modified activated carbon were analyzed using a PerkinElmer 2400 elemental analyzer. The results showed that the activated carbon did not contain nitrogen and sulfur elements. The percentage of nitrogen in the modified activated carbon was 4.63%, and the percentage of sulfur was 3.25%. Therefore, it can be seen that polyaspartic acid and 3-hydroxypropanesulfonic acid reacted and successfully modified the activated carbon.

[0037] 2. Preparation of mineral additives

[0038] Step T1: 3.6 g of tourmaline powder was dispersed in dimethyl sulfoxide to form a uniform dispersion, 2.4 g of mercaptosuccinic acid and 0.5 g of p-toluenesulfonic acid were added, and the mixture was stirred and mixed uniformly, and the temperature was raised to 90° C., and the mixture was reacted for 4 h, and then filtered, washed, and dried to obtain modified tourmaline powder;

[0039] Step T2: Add 3.2 g of modified tourmaline powder to N,N-dimethylformamide, and after uniform dispersion, add 2 g of 3-aminopyridine, 0.3 g of dicyclohexylcarbodiimide and 0.1 g of 4-dimethylaminopyridine. After reacting for 4 hours, discharge, wash and dry to obtain a mineral additive component.

[0040] The infrared test of mineral additive components was carried out using Fourier infrared spectrometer, such as Figure 1As shown in the figure, analysis shows that in the infrared spectrum of the mineral additive component, 3425cm -1 The absorption peak of NH in amide appeared at 2524 cm -1 The absorption peak of thiol SH appeared at 1728 cm -1 The absorption peak of ester group C=O appeared at 1662 cm -1 The absorption peak of C=O in amide appeared at 1430 cm -1 The absorption peak of CN appeared at 1276 cm -1 The absorption peak of BO appeared at 1004 cm -1 The Si-O absorption peak appears at

[0041] 3. Preparation of natural composite rubber

[0042] Add 2.5g agar and 2.5g arabinoxylan into deionized water, raise the temperature to 65°C, stir for 1h, add 1.4g sodium tripolyphosphate, continue stirring for 3h, cool to room temperature, discharge and obtain natural composite glue.

[0043] A 180° peeling test was performed on tinplate coated with natural composite glue, agar and arabinoxylan on one side using a universal testing machine. The tinplate coated with natural composite glue, agar and arabinoxylan on one side was attached to the tape, and the other side of the tinplate was affixed with double-sided tape and fixed on a glass slide to test the bonding performance. The test is shown in the following table:

[0044] Agar Arabinoxylan Natural composite glue Peel force (N / cm) 1.32 1.28 3.62

[0045] It can be seen from the above table that the natural composite glue structure contains a cross-linked network structure, so the bonding performance is stronger than that of agar and arabinoxylan, and a small amount of addition can be used to firmly and stably bond the modified activated carbon, mineral additives, calcium carbonate and zeolite powder.

[0046] Example 1

[0047] Manufacturing of activated carbon materials

[0048] Step 1: Add 35g of modified activated carbon, 10g of mineral additive components, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 150r / min for 10min, then add 4g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 1h to obtain a mixed base material;

[0049] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 70°C for 4 hours, and cool it to room temperature to obtain the activated carbon material.

[0050] Example 2

[0051] Manufacturing of activated carbon materials

[0052] Step 1: Add 40g of modified activated carbon, 12g of mineral additive components, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 200r / min for 15min, then add 5g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 1.5h to obtain a mixed base material;

[0053] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 80°C for 4.5 hours, and cool it to room temperature to obtain the activated carbon material.

[0054] Example 3

[0055] Manufacturing of activated carbon materials

[0056] Step 1: Add 45g of modified activated carbon, 14g of mineral additive components, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 250r / min for 20min, add 6g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 2h to obtain a mixed base material;

[0057] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 85°C for 5 hours, and cool it to room temperature to obtain the activated carbon material.

[0058] Example 4

[0059] Manufacturing of activated carbon materials

[0060] Step 1: Add 50g of modified activated carbon, 15g of mineral additive components, 4g of calcium carbonate and 6g of zeolite powder into a blender, stir and mix at a stirring rate of 300r / min for 30min, then add 8g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 3h to obtain a mixed base material;

[0061] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 90°C for 6 hours, and cool it to room temperature to obtain the activated carbon material.

[0062] Comparative Example 1

[0063] Manufacturing of activated carbon materials

[0064] Step 1: Add 45g of modified activated carbon, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 250r / min for 20min, then add 6g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 2h to obtain a mixed base material;

[0065] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 85°C for 5 hours, and cool it to room temperature to obtain the activated carbon material.

[0066] Comparative Example 2

[0067] Manufacturing of activated carbon materials

[0068] Step 1: Add 45g of activated carbon, 14g of mineral additive components, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 250r / min for 20min, then add 6g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 2h to obtain a mixed base material;

[0069] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 85°C for 5 hours, and cool it to room temperature to obtain the activated carbon material.

[0070] Comparative Example 3

[0071] Manufacturing of activated carbon materials

[0072] Step 1: Add 45g of modified activated carbon, 14g of tourmaline powder, 3g of calcium carbonate and 4g of zeolite powder into a blender, stir and mix at a stirring rate of 250r / min for 20min, then add 6g of natural composite rubber, keep the stirring rate unchanged, and continue stirring for 2h to obtain a mixed base material;

[0073] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 85°C for 5 hours, and cool it to room temperature to obtain the activated carbon material.

[0074] Comparative Example 4

[0075] Manufacturing of activated carbon materials

[0076] Step 1: Add 45g activated carbon, 3g calcium carbonate and 4g zeolite powder into a blender, stir and mix at a stirring rate of 250r / min for 20min, then add 6g natural composite rubber, keep the stirring rate unchanged, and continue stirring for 2h to obtain a mixed base material;

[0077] Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 85°C for 5 hours, and cool it to room temperature to obtain the activated carbon material.

[0078] Detection

[0079] The acidified heavy metal soil was taken, impurities in the soil were removed, the soil was air-dried and crushed, and the soil was passed through an 80-mesh sieve to obtain the test soil.

[0080] a: The test soil was added to deionized water to prepare a mixture with a solid content of 400 g / L in 1000 mL. The initial pH value of the test soil was measured using a soil pH tester. The test soil was evenly divided into 8 test groups. 4 g of the activated carbon material prepared in Examples 1 to 4 and Comparative Examples 1 to 4 was added to each test group. The mixture was evenly mixed and placed in a shock box. After shaking at room temperature for 16 hours, the mixture was allowed to stand. The supernatant was taken after 15 days and 45 days. The pH value of the test group was measured using a soil pH tester. The test results are shown in Table 1:

[0081] Table 1

[0082] Initial pH 15-day pH 45 days pH Example 1 4.92 5.72 6.95 Example 2 4.92 5.78 7.01 Example 3 4.92 5.80 7.03 Example 4 4.92 5.75 6.98 Comparative Example 1 4.92 5.22 5.33 Comparative Example 2 4.92 5.68 6.93 Comparative Example 3 4.92 5.41 6.15 Comparative Example 4 4.92 5.13 5.25

[0083] As can be seen from Table 1, the activated carbon materials manufactured by Examples 1 to 4 of the present invention can increase the pH value of acidified heavy metal soil. Comparative Examples 1 and 4 do not add mineral additives, so the effect of improving the pH value is very poor. Comparative Example 3 adds unmodified tourmaline powder, which has a poor effect on improving the pH value.

[0084] b: The test soil was added to deionized water to prepare a mixture with a solid content of 400 g / L in 1000 mL, 1 mol / L hydrochloric acid was added to the mixture, and after stirring for 90 min, the heavy metal ion content was tested as M0, and then the mixture was evenly divided into 8 test groups, and 4 g of the activated carbon materials prepared in Examples 1 to 4 of the present invention and Comparative Examples 1 to 4 were added to the test groups respectively, and the mixture was stirred evenly. After standing for one week, the supernatant was taken and the heavy metal ion content was tested again as M1. According to the adsorption rate = [(M0-M1) / M0] × 100%, the results are shown in Table 2:

[0085] Table 2

[0086] Adsorption rate / % Example 1 97.4 Example 2 97.9 Example 3 98.2 Example 4 97.6 Comparative Example 1 78.5 Comparative Example 2 75.6 Comparative Example 3 80.4 Comparative Example 4 62.2

[0087] It can be seen from Table 2 that the activated carbon materials manufactured by Examples 1 to 4 of the present invention have excellent heavy metal adsorption effects. Comparative Example 1 adds modified activated carbon but does not add mineral additives, and cannot utilize the abundant chelating groups in the mineral additives to adsorb heavy metals. Therefore, the amount of heavy metal adsorption is small and the adsorption effect is poor; Comparative Example 2 adds activated carbon and mineral additives, and the activated carbon is not modified, has few adsorption sites, and has a low adsorption capacity, so the adsorption effect is poor; Comparative Example 3 adds modified activated carbon and tourmaline powder, and the tourmaline powder has no chelating groups on its surface, and has poor adsorption capacity for heavy metals, so the adsorption effect is poor; Comparative Example 4 only adds activated carbon, and the adsorption effect is the worst.

[0088] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An activated carbon material for adsorbing heavy metals in soil, characterized in that: The invention comprises the following raw materials in parts by weight: 35-50 parts of modified activated carbon, 10-15 parts of mineral additive components, 4-8 parts of natural composite rubber, 2-4 parts of calcium carbonate and 3-6 parts of zeolite powder.

2. The activated carbon material for adsorbing heavy metals in soil according to claim 1, characterized in that: The preparation method of the modified activated carbon comprises the following steps: Step S1: adding activated carbon to concentrated nitric acid, stirring and mixing for 2-4 hours, filtering, washing, and drying to obtain pretreated activated carbon; Step S2: Add the pretreated activated carbon and polyaspartic acid to N,N-dimethylformamide, mix evenly, and ultrasonically vibrate for 10-30 minutes, then add 3-hydroxypropanesulfonic acid, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, start stirring, control the stirring rate to 500-650r / min, stir for 4-6 hours, separate the product, wash, and dry to obtain modified activated carbon.

3. The activated carbon material for adsorbing heavy metals in soil according to claim 2, characterized in that: In step S1, the mass fraction of concentrated nitric acid is 60-65%.

4. The activated carbon material for adsorbing heavy metals in soil according to claim 2, characterized in that: In step S2, the ultrasonic frequency during the ultrasonic oscillation is 60-80 kHz.

5. The activated carbon material for adsorbing heavy metals in soil according to claim 1, characterized in that: The preparation method of the mineral additive component comprises the following steps: Step T1: Disperse tourmaline powder in dimethyl sulfoxide to form a uniform dispersion, add mercaptosuccinic acid and a catalyst, stir and mix evenly, raise the temperature to 90-95° C., react for 3-5 hours, filter, wash, and dry to obtain modified tourmaline powder; Step T2: Add the modified tourmaline powder into N,N-dimethylformamide, and after uniform dispersion, add aminopyridine compounds, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react for 3-5 hours, discharge, wash, and dry to obtain a mineral additive component.

6. The activated carbon material for adsorbing heavy metals in soil according to claim 5, characterized in that: In step T1, the catalyst is p-toluenesulfonic acid or calcium methanesulfonate.

7. The activated carbon material for adsorbing heavy metals in soil according to claim 5, characterized in that: In step T2, the aminopyridine compound is any one of 2-aminopyridine, 3-aminopyridine or 4-aminopyridine.

8. The activated carbon material for adsorbing heavy metals in soil according to claim 1, characterized in that: The preparation method of the natural composite rubber is as follows: Add agar and arabinoxylan into deionized water, raise the temperature to 60-70°C, stir and mix for 0.5-1h, add sodium tripolyphosphate, continue stirring for 2-4h, cool to room temperature, discharge, and obtain a natural composite glue.

9. A process for manufacturing an activated carbon material for adsorbing heavy metals in soil as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Add modified activated carbon, mineral additive components, calcium carbonate and zeolite powder into a mixer, stir and mix for 10-30 minutes, add natural composite rubber, keep the stirring rate unchanged, and continue stirring for 1-3 hours to obtain a mixed base material; Step 2: Place the mixed base material into a mold, extrude it into shape, place it in a drying oven, dry it at 70-90°C for 4-6 hours, and cool it to room temperature to obtain the activated carbon material.

10. The manufacturing process of an activated carbon material for adsorbing heavy metals in soil according to claim 9, characterized in that: In step 1, the stirring rate is 150-300 r / min.

Citation Information

Patent Citations

  • A modified sludge activated carbon heavy metal adsorption material

    CN109231758B

  • Preparation method of soil stabilizer for remediation of heavy metal contamination

    CN106147781A

  • Magnetic polyethyleneimine grafted carbon nanotube composite adsorption material and preparation method thereof

    CN112844312A

  • Stabilizer prepared from organic waste and use method thereof

    CN112852432A

  • Polyfunctional group modified loofah sponge heavy metal adsorbent and preparation method thereof

    CN118162115A